Konstruksi Solidaritas Sosial Berbasis Ikatan Banjar Solo Timur Pada Masyarakat Hindu Di Surakarta - I Nyoman Suendi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
The kinship system based on the Banjar bonding system is a model of social institutions that have been applied by Hindu communities in Surakarta since historical times. Social institutions are used as a vehicle to form a traditional social order. In Hindu social life the social institutions are able to expedite the process of implementing Hinduism because in it are able to realize social solidarity internally among Hindu communities in Surakarta. In connection with this matter in this study raised three problems to study the construction of social solidarity, namely (1) What is the pattern of social solidarity construction based on the Banjar bonding system in Hindu communities in Surakarta? (2) What is the mechanism of social solidarity construction based on the Banjar bond system in Hindu communities in Surakarta? Based on observations obtained that the pattern of social solidarity construction based on the banjar bond system is related to the form of social institutions that are used as a vehicle for completing religious social activities carried out by the Hindu community in Surakarta. Social institutions were formed since the historical period, namely when in the early days of the existence of the ethnic Balinese Hindu community in Surakarta around 1970. The social system of Banjar ties was played as a vehicle to expedite the process of Hinduism, especially in the realm of the Manusa Yajna and Pitra Yajna ceremonies. The banjar bonding system is used in the implementation of manusa yajna ceremonies, such as in the implementation of marriage ceremonies, while in the implementation of pitra yajna ceremonies, especially in ceremonies relating to burial or cremation according to the Hindu religious belief system. The mechanism of social solidarity construction based on the Banjar bonding system is based on the basic elements that form the means of forming social solidarity in the banjar bonding system such as bonds of bonds, the similarity of belief systems adopted, family ties based on marriage and similar interests. The bond of association is an emotional bond that occurs primarily in the emotions of brotherhood. The fraternity emotion starts from a sense of adimp metimpal (suitable siblings) so as to create a sense of mutual respect, compassion, fostering each other and feel the same fate and continuity.